Metabolic impact of cardiac hormon therapy - Pragier, Uriel (Revista de la Sociedad Argentina de Diabetes, 2023)
Gender dysphoria (DG) implies a discordance between the gender assigned at birth and the self-perceived one. Male transgender or male transsexual (FTM) are identified with the male gender and have been assigned as female at birth. Transgender women or transsexual women (MTF) are identified as women but have been assigned as men at birth. There are those who do not seek extreme masculinization or feminization, which allows the term "sexual diversity" to cover these cases.